A Theoretical Study of The Influence of Donor Sensitize Dye on Performance of Dye-sensitized Solar Sells DSSCs - Hadi J. M. Al-Agealy; Al Maadhede, Taif Saad; Mohammad Hafizuddin Jumali; Chi Chin Yap (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this paper, a theoretical study was introduced to discussion the Influence of donor senstizer on efficiency of solar cell with clear focusing on dye senstized solar cell DSSCs applications was presented. Use of donor as -sensitizer dye in solar cells was a viable contender in photovoltaics due to their spectrum of excited state to transfer more elkectrons to conduction band of semiconductor .In this study, two systems Alq3/ZnO and D149/ZnO devices taken with same two solvents .Transtion energy ,coupling strength and transtion parameters are used to calculate the electron current density , it uses to calculate the photovoltic characteristic I-V ,fill factor and the efficiency of the solar cell. Especially, the largest performance was for the both D149/ ZnO and Alq3/ZnO solar cells based on Acetonitrile as a solvent with electron current density of (430 0.329-13.8) mA/cm^2 between (1-6) V and produced the highest efficiency calculated 2.593 and 0.938for the both solar cell was corresponds to the lowest efficiency about 0.536 for Alq3/ZnO with Ethanol solvent